SOME RECOMMENDATIONS FOR STUDENTS HOW TO WRITE “INFORMAL LETTER” (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Every person writes a letter at some point of time in his life. Letters not only carry formal discourses but are also means of friendly conversations. How language and vocabulary is used in a letter reflects the skills and finesse of the writer as well. Therefore, it is essential to master the skill of writing a good letter from an early age. In this article we discuss about some tips for informal letter writing.